Analisis Kinerja Keuangan Pada Perusahaan Daerah Air Minum Tirta Tawar - Kurniadi Rwd (CERED Indonesia Institute, 2021)
This research is expected to find out how the financial performance of the Regional Drinking Water Company of Tirta Tawar, Central Aceh Regency, in terms of liquidity, activity, solvency, profitability. This research uses qualitative methods with case studies. The object and subject of this study are financial performance measured using financial ratios. Current Ratio value is 0.55 with PDAM financial standards based on the Ministerial Decree, namely> 1.50 - 1.75 with a weight (4) with a good assessment. The calculation value with the standard Kepmen is a difference of 0.95. This means that the company must improve and optimize current assets and increase sales and parse accounts receivable so that current assets can increase.